Gender diversity in teams - Ghazala Azmat (IZA World of Labor, 2019)
Women's representation on corporate boards, political committees, and other decision-making teams is increasing, this is in part because of legal mandates. Evidence on team dynamics and gender differences in preferences (for example, risk-taking behavior, taste for competition, prosocial behavior) shows how gender composition influences group decision-making and subsequent performance. This works through channels such as investment decisions, internal management, corporate governance, and social responsibility.
Keywords: J16; M50; L25; 330; gender; team diversity; performance; decision-making